The impact of shortage construction materials in construction industry at Southern Sarawak / Jordan Evin Guntor - Guntor, Jordan Evin (2020)
Construction industry is one of the most significant sectors in Malaysia for the role in expansion and economic progression. Therefore, construction materials are very important to the success of the project. Hence, issue appear from the shortage of construction materials in construction industry. The construction industry not taking serious in shortage of materials because they do not know the impact of shortage materials towards the construction industry. The aim of the research is to investigate the impact of shortage construction materials in construction industry at Southern Sarawak. This paper consists of three objectives to identify types of shortage materials in construction industry, to study the demand and supply of construction materials at Southern Sarawak and to determine the impact of shortage materials at Southern Sarawak.